Linking Pre-Services Physics Teachers' Views About Experimental Physics with Their Lab Report Scores - Ogi Danika Pranata; Deny Pra Setyo; Nora Indrasari (Experiment: Journal of Science Education, 2026)
The purpose of this study was to examine the relationship between pre-services physics teachers’ views of experimental physics and the quality of their laboratory reports. A quantitative study with a descriptive and correlational design involving 26 pre-services physics teachers enrolled in a basic physics course focusing on kinematics experiments was conducted. The participants worked in small groups to design and conduct experiments, analyze the data, and write laboratory reports. The reports were assessed based on three indicators: systematics and completeness, content and conceptual depth, and writing style and neatness. Pre-service physics teachers’ views about experimental physics were measured using the Colorado Learning Attitudes about Science Survey for Experimental Physics (E-CLASS). Data were analyzed using descriptive statistics and Spearman’s rho correlation. The main finding shows that there is no significant correlation between E-CLASS scores and the laboratory reports quality. This indicates that favorable views about experimental physics do not necessarily translate into better performance in scientific reporting. These findings suggest a gap between epistemological beliefs and scientific communication skills, where understanding the nature of experimental physics does not automatically lead to the ability to express it effectively in written form. Therefore, laboratory instruction in teacher education programs should explicitly integrate support for experimental reasoning, data interpretation, and scientific writing, rather than emphasizing procedural completeness alone. Future research should involve larger and independent samples, apply individual-level assessment of laboratory performance, and examine instructional designs that intentionally connect epistemological development with experimental practice and scientific communication.